Exploring the Impact of Fear of Missing Out (FoMO) on Youth Shopping Intentions in Social Commerce Landscape - Bui Thanh Khoa; Nguyen Minh Tuan; Nguyen Duy Phuong (Qubahan Academic Journal)
This study explored the influence of Fear of Missing Out (FoMO) on youths’ shopping intentions within the social commerce environment of TikTok. The background emphasized the growing prevalence of social media platforms as retail channels and the potential impact of FoMO on consumer behavior. The objective was to examine the relationships between FoMO, attitude towards behavior, subjective norm, perceived behavioral control, and shopping intentions on TikTok. A quantitative research design using a survey methodology was employed. Data were collected from young TikTok users and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings demonstrated that FoMO favorably affected shopping intentions, both directly and indirectly, by negatively impacting perceived behavioral control. According to the Theory of Planned Behavior, attitude, and subjective norms were identified as significant determinants of shopping intentions. Perceived behavioral control, however, did not demonstrate a significant correlation with shopping intentions. The study revealed that FoMO significantly influences the purchase intentions of teenagers on TikTok, providing essential information for marketers aiming to capitalize on this phenomenon in social commerce initiatives.